Hydropower plans in eastern and southern Africa increase risk of concurrent climate-related electricity supply disruption. Issue 12 (December 2017) - Conway, Declan; Dalin, Carole; Landman, Willem; Osborn, Timothy
Abstract Hydropower comprises a significant and rapidly expanding proportion of electricity production in eastern and southern Africa. In both regions, hydropower is exposed to high levels of climate variability and regional climate linkages are strong, yet an understanding of spatial interdependences is lacking. Here we consider river basin configuration and define regions of coherent rainfall variability using cluster analysis to illustrate exposure to the risk of hydropower supply disruption of current (2015) and planned (2030) hydropower sites. Assuming completion of the dams planned, hydropower will become increasingly concentrated in the Nile (from 62% to 82% of total regional capacity) and Zambezi (from 73% to 85%) basins. By 2030, 70% and 59% of total hydropower capacity will be located in one cluster of rainfall variability in eastern and southern Africa, respectively, increasing the risk of concurrent climate-related electricity supply disruption in each region. Linking of nascent regional electricity sharing mechanisms could mitigate intraregional risk, although these mechanisms face considerable political and infrastructural challenges. Hydropower is critical to eastern and southern Africa but it is at risk from climate variability. Conway et al. examine river basins and rainfall variability to explore potential hydropower disruption for present and planned generation sites, highlighting the risks to supply and their spatial interlinkages.